If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -6) * 10 = 90 Reorder the terms: (-6 + n) * 10 = 90 Reorder the terms for easier multiplication: 10(-6 + n) = 90 (-6 * 10 + n * 10) = 90 (-60 + 10n) = 90 Solving -60 + 10n = 90 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 10n = 90 + 60 Combine like terms: -60 + 60 = 0 0 + 10n = 90 + 60 10n = 90 + 60 Combine like terms: 90 + 60 = 150 10n = 150 Divide each side by '10'. n = 15 Simplifying n = 15
| -2(6s+9)=2(s-4) | | (11p^3-9p^2-6p)+(10p^2-8p+4)= | | 24-19= | | 4x^2-19x+36=2x+9 | | 10+2(z-5)=-5z+2 | | 10+2(2-5)=-52+2 | | 2x+3-7=0 | | (-8x^2-11x-15)+(4x^2-12x+13)= | | 11=-8x+27 | | x+9=5[4x-2] | | x+2-2=0 | | 8t^2-25t+18=0 | | -60=12m | | 2/5+25=10 | | 2(6x-1)=47 | | 2/5.25=10 | | (7m^2-9m-8)+(5m^2+10m+4)= | | 4x-5=7x-2 | | 21+7(z-3)=6z+5 | | 2-6n=-2 | | 3x+x=2x-6 | | 21+7(z-3)=6z-5 | | (5x+3)(7x-4)= | | -2(7-c)=6 | | 5x+3(x-1)=-27 | | 2x+4=3x+12 | | 10-x=10 | | 3(2z-3)-3(2-3z)=6 | | 2x+6=5x-7 | | 2x+8-8x+9=17-x | | 9+2(2n-10)=1 | | 12a-18ab-10ab+15b= |